2009
DOI: 10.1128/cvi.00253-08
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Promoter, Gene Copy Number, and Preexisting Immunity on Humoral and Cellular Responses to a Vectored Antigen Delivered by a Salmonella enterica Vaccine

Abstract: Attenuated Salmonella strains are currently in production as vaccines for protection of animals against salmonellosis. Such commercial strains offer the potential to deliver heterologous antigen to protect animals against other diseases. One vaccine strain, attenuated Salmonella enterica serovar Typhimurium (STM-1), was tested for the ability to deliver ovalbumin and to induce immune responses in mice. Two vaccine trials were performed testing the influence of promoter choice, the location of the encoding DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 60 publications
(50 reference statements)
1
8
0
Order By: Relevance
“…The presence of opsonizing antibodies should mean a higher level of bacterial uptake, leading to higher presentation to the immune system and therefore a better immune response. We have previously shown that this is indeed the case (Saxena et al , 2009) (depicted in Fig. 2).…”
Section: Concluding Remarks and Perspectivesupporting
confidence: 66%
See 3 more Smart Citations
“…The presence of opsonizing antibodies should mean a higher level of bacterial uptake, leading to higher presentation to the immune system and therefore a better immune response. We have previously shown that this is indeed the case (Saxena et al , 2009) (depicted in Fig. 2).…”
Section: Concluding Remarks and Perspectivesupporting
confidence: 66%
“…In these subjects, humoral responses were moderately elevated in pre-exposed individuals. Similarly, Saxena et al (2009) indicated higher humoral and T cell responses in mice pre-exposed to homologous or heterologous Salmonella strains. The interleukin 4 (IL4) response was significantly higher when the animal host was exposed to the homologous strain, whereas pre-exposure to a related species did not have such an impact on IL4 responses.…”
Section: Effects Of Prior Immunological Exposure To Vectors – Bacterimentioning
confidence: 91%
See 2 more Smart Citations
“…The attenuated Salmonella strains by Hoiseth and Stocker 4 has led to the extensive development of vaccines for typhoid fever in humans 5 , 6 and salmonellosis in calves, 7 - 9 pigs, 10 - 13 and chickens 14 - 16 . Moreover, such live vaccines also allow for the expression of heterologous genes from other pathogenic organisms that can stimulate both humoral and cell-mediated arms of immunity 17 - 19 . When these are attenuated, one unique feature of live vector vaccines is their ability to stimulate both the mucosal and systemic immune compartments of the host while having limited capacity for growth and pathogenicity.…”
Section: Introductionmentioning
confidence: 99%